2010
DOI: 10.1038/onc.2010.16
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor regulates MET levels and invasiveness through hypoxia-inducible factor-1α in non-small cell lung cancer cells

Abstract: Recent studies have established that amplification of the MET proto-oncogene can cause resistance to epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) in non-small cell lung cancer (NSCLC) cell lines with EGFR-activating mutations. The role of non-amplified MET in EGFR-dependent signaling before TKI resistance, however, is not well understood. Using NSCLC cell lines and transgenic models, we demonstrate here that EGFR activation by either mutation or ligand binding increases MET gene ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 57 publications
3
69
0
Order By: Relevance
“…15,16 To test whether MET reacts to the interaction of EPAS1 and T790M EGFR, we expressed T790M EGFR and EPAS1 in HCC827 cells simultaneously and examined MET protein levels using anti-c-Met antibody. As previously reported, expression of wild-type and T790M EGFR alone was sufficient to trigger MET amplification, 25 even in the absence of EPAS1 (Fig. 3A, lanes 1 and 2 from left).…”
Section: Epas1 and T790m Egfr Interaction Up-regulates Met Pathway Insupporting
confidence: 57%
See 2 more Smart Citations
“…15,16 To test whether MET reacts to the interaction of EPAS1 and T790M EGFR, we expressed T790M EGFR and EPAS1 in HCC827 cells simultaneously and examined MET protein levels using anti-c-Met antibody. As previously reported, expression of wild-type and T790M EGFR alone was sufficient to trigger MET amplification, 25 even in the absence of EPAS1 (Fig. 3A, lanes 1 and 2 from left).…”
Section: Epas1 and T790m Egfr Interaction Up-regulates Met Pathway Insupporting
confidence: 57%
“…25 To explore if there are other factors mediating EGFR-MET interaction, we carried out a genome-wide search for HIF-1a homologs and EPAS1 (NCBI Reference Sequence: NP_001421.2) was returned as the top hit with 48% amino acid sequence identity (Fig. 1A).…”
Section: Epas1 Is a Hif-1a Homolog And Directly Interacts With T790m mentioning
confidence: 99%
See 1 more Smart Citation
“…EGFR-activating mutations have been found to associate with elevated levels of MET in both NSCLC transgenic murine models and clinical samples [138]. Using NSCLC cell lines, Xu et al have shown that the HIF-1α/MET axis plays an important role in regulating invasiveness induced not only by hypoxia but also by EGFR signaling.…”
Section: Metmentioning
confidence: 99%
“…As mentioned in section 1.1., hypoxia is a regulator of HGF, presumably through HIF-1α activity [55]. In this respect, Xu et al suggested that EGFR-activating mutations could promote production of HGF through HIF-1α and thus EGFR/HIF-1α activation may not only regulate MET levels, but also have an impact on MET signal transduction [138].…”
Section: Metmentioning
confidence: 99%